Educational Objectives In Skill Of Writing Arabic To Other Speakers At The Level Of A1 And A2 In Perspective Of The Common European Framework For Teaching Languages - Talqis Nurdianto; Zainal Abidin Hajib; Noor Azizi Ismail (UNIVERSITAS MUHAMMADIYAH MALANG INDONESIA, 2024)
Jurnal Lisanudhad Vol. 06 No. 02, Desember 2019